Hydration status measured by BCM: A potential modifiable risk factor for peritonitis in patients on peritoneal dialysis. Issue 5 (May 2016) - Santhakumaran, Territa; Samad, Nasreen; Fan, Stanley L
Abstract: Aim: Peritoneal dialysis peritonitis and fluid overhydration (OH) are frequent problems in peritoneal dialysis. The latter can cause gut wall oedema or be associated with malnutrition. Both may lead to increased peritonitis risk. We wished to determine if OH is an independent risk factor for peritonitis (caused by enteric organisms). Methods: Retrospectively study of patients with >2 bioimpedance assessments (Body Composition Monitor). We compared peritonitis rates of patients with above or below the median time‐averaged hydration parameter (OH/extracellular water, OH/ECW). Multivariate analysis was performed to determine independent risk factors for peritonitis by enteric organism. Results: We studied 580 patients. Peritonitis was experienced by 28% patients (followed up for an average of 17 months). The overall peritonitis rate was 1:34 patient months. Patients with low OH/ECW values had significantly lower rates of peritonitis from enteric organisms than overhydrated patients (incident rate ratio 1.53, 95% confidence interval 1.38–1.70, P < 0.001). Hydration remained an independent predictor of peritonitis from enteric organisms when multivariate model included demographic parameters (odds ratio for a 1% increment of OH/ECW was 1.05; 95% confidence interval 1.01–1.10, P < 0.02). However, including biochemical parameters of malnutrition reduced the predictive power of overhydration. Conclusion: We found an association between overhydration and increased rates of peritonitis. While this may partly be due to the high co‐morbidity of patients (advanced age and diabetes), on multivariate analysis, only inclusion of nutritional parameters reduced this association. It remains to be determined if overhydration will prove to be a modifiable risk factor for peritonitis or whether malnutrition will prove to be more important. Summary at a Glance: Fluid overload is a very important risk factor on all cause mortality and residual function. This paper tried to investigate how to measure a fluid status and avoid potential modifiable risk factor for peritonitis in patients on peritoneal dialysis. It is great benefit for peritoneal dialysis doctors in their clinical practice.